Forecasting the Use of Argon Mix (Ar-Co2) in the FCAW Welding Process Using the Moving Average and Single Exponential Smoothing Methods - Wildan; Anis Siti Nurrohkayati (Universitas Muhammadiyah Sidoarjo, 2022)
Welding has a very important role in metal engineering and repair, therefore technological developments in the increasingly advanced construction sector cannot be separated from welding. FCAW (Flux Cored Arc Welding) is a welding process that is often used in the industrial world where the welding process uses an electric arc as a heat source to melt metal, using gas as a shield and electrodes as a filler. This study analyses the use of shielding gas by observing the welding process and then taking the welding result data which is then calculated using the moving average forecasting method and single exponential smoothing. The data from the analysis obtained an average amperage of 257, argon flow rate of 34.45 L/min with a time of 25.31 seconds using argon as much as 265.90 psi or in one argon mix tube with the content of 2.175 psi it took 3 hours 45 minutes total welding time